Global trends and future prospects of COVID-19 and physical activity: Bibliometric analysis - Toktas, Nese; Kose, Elif; Lapa, Tennur-Yerlisu; Kaas, Evren-Tercan; Yucel, Ali Serdar; Derman, Suleyman (Lippincott Williams & Wilkins, 2023)
Background:Containment measures implemented during the COVID-19 pandemic have led to drastic changes in daily life and effects on health behaviors such as decrease in physical activity (PA) levels. This study aims to present a general framework to researchers on COVID-19 and PA research in relation with changes in studies within years, current trend topics, gaps in the research field and possible future trends.Methods:A total of 1819 articles indexed in the WoS core collection database were analyzed according to publication year, citation, country and institution collaborations, coword, co-citation networks, concept-topic trends and topic clusters using bibliometric analysis.Results:The most productive country was the USA(n = 335), and the most productive institution was University of London in UK (n = 38). The most cited publication was the study by Ammar et al, (2020) (n = 188). In 2020, the most popular topics were PA and health meanwhile in 2021 behavior, lifestyle, social media and in 2022 habits, long COVID, sleep quality topics were in the foreground. Studies in 2023 focus on how COVID-19 affects PA habits and the associations between COVID-19-based anxiety and sleep patterns. These studies focused especially on effects of sport participation on life quality, diet, depression, mental health on young athletes, children, adolescent persons, older adult groups.Conclusions:An important gap in the study area is research on effect of changing lifestyle due to pandemic on individuals and the society during the Post COVID-19 period. If benefits of PA will not be limited to only physical benefits and psychological emotional, cognitive and social benefits are also taken into consideration, it is important that researchers conduct long-term and widescale observations.
Keywords: bibliometrics; coronavirus; COVID-19; physical activity; SARS-CoV-2